Patient Characteristics and Clinical Outcomes with Low-Dose Dabigatran - Ebrahimi, Ramin; Han, Janet K.; Goe, Seung H.; Treadwell, Michelle; Feliciano, Zenaida (Frontiers in Cardiovascular Medicine, 2017)
Background/Aims: Dabigatran, an oral direct thrombin inhibitor, is used in patients with non-valvular atrial fibrillation to reduce thromboembolic events. Whereas the 150 mg dosing regimen has been extensively studied in clinical setting, to date there is no clinical data on the 75 mg (Low Dose, “LD”) regimen. In this study we evaluated patient characteristics and clinical outcomes in 49 patients treated with LD dabigatran. Methods: Electronic medical records were utilized to compare patients from one medical center treated with LD dabigatran to those from the warfarin arm of the RE-LY trial. Results: Compared to those from the warfarin arm of the RE-LY trial, the LD dabigatran patients were significantly older (82.6 vs 71.6 years p<0.001), had higher prevalence of diabetes (42.9% vs 23%, p<0.001), were predominantly male (100% vs 63.3% p<0.001) and had higher CHADS2 score (2.8 vs 2.1 p< 0.001). Only 9 (18%) patients had creatinine clearance (CrCl) of <30 ml/min and none were on concomitant medications that required dose adjustment to LD dabigatran. During a mean follow up of 10.1 months, there were no thromboembolic events, no cerebrovascular events and seven bleeding events in the LD dabigatran group of which only two required blood transfusion. Conclusions: In this database most patients received LD dabigatran based on characteristics not related to the approved indications for this dose. The exploratory clinical outcomes of using LD dabigatran outside of the current approved indications are promising in this high risk population and deserve further investigation to better understand the role of LD dabigatran in clinical practice.